The Effectiveness of Instagram as a Medium for Learning English Vocabulary - Rosinta, Rosinta; Ramadhan Hamid, Ade Ismail; Rachman, Dzul (JELITA, 2025)
This study aims to see how effective the use of Instagram Story as an innovative way to help students learn English vocabulary in class VIII MTs Muhammadiyah 1 Samarinda. This study was conducted with a quantitative approach and used a pre-experiment design, specifically one-group pre-test and post-test. The study participants consisted of 20 students who took the vocabulary test before and after the treatment. The test was in the form of multiple choice questions which aimed to measure how well they understood the vocabulary. In three meetings, students were taught to use Instagram Story features such as pictures, quizzes, and charades to learn English vocabulary. The results showed that the students' average score increased from 7.15 in the pre-test to 9.35 in the post-test. The paired t-test analysis showed a t-count of -5.311 with a significance of less than 0.001, which means there was a highly significant difference before and after the treatment. These findings prove that Instagram Stories serve as an effective learning medium that significantly improves students' English vocabulary mastery.